Spatiotemporal trends of disease burden of edentulism from 1990 to 2019: A global, regional, and national analysis - Li, Xiao; Man, Jinyu; Chen, Hui; Yang, Xiaorong (Frontiers in Public Health, 2022)
Background: Understanding the spatiotemporal trends in disease burden of edentulism is critical to reducing disease burden of edentulism and deploying medical resources. We assessed the changing patterns of disease burden of edentulism at global, regional and national levels from 1990 to 2019. Methods: Data on incident cases, prevalent cases, disability-adjusted life years (DALYs), and age-standardized rates (ASRs) of edentulism were extracted from the Global Burden of Disease 2019 Study. We calculated the estimated annual percentage change (EAPC) to quantify spatiotemporal trends in the ASRs of edentulism. Results: In 2019, the number of prevalent cases and DALYs of edentulism were 35.2 million and 9.6 million, and the ASPR and ASDR were 43.12/1000 and 1.18/1000, with EAPCs of -0.18 [95% confidence interval (CI): -0.28, -0.09] and -0.16[95% CI: -0.26, -0.07] from 1990 to 2019 respectively. Females and the elderly had a higher burden of edentulism. Although the ASPR, ASDR and ASIR in the high SDI, high-middle SDI, and middle SDI regions showed a decreasing or stable trend, the absolute disease burdens of edentulism in these regions were still high. Although the absolute disease burdens of low SDI and low-middle SDI were low, their ASPR and ASDR showed an upward trend. In countries with high initial disease burden or high SDI, ASPR, ASDR, and ASIR showed stable or declining trends. Conclusions: The absolute disease burden due to edentulism was increasing in many countries and regions. Countries should reduce the disease burden caused by edentulism by adopting measures including the prevention and treatment of dental caries and periodontal disease.